Water Quality Control System In Goldfish Aquarium Using Fuzzy Method - Rizky Rizwansyach; Isa Hafidz; Chaironi Latif (Journal of Computer Electronic and Telecommunication, 2025)
Considering the beauty and unique characteristics of goldfish as ornamental fish, keeping goldfish in an aquarium is a popular hobby among the community. However, some people face challenges in maintaining goldfish that must be controlled manually. In this work, the author proposes to create a water quality control system for goldfish aquariums using fuzzy logic. This system uses the E-201-C pH sensor to measure the water's pH level, the SEN-0189 turbidity sensor to detect water turbidity, an ultrasonic sensor to maintain water height, and the ESP32 as the microcontroller. In the pH control, a mini pump is used, which activates when the pH level is >9 to lower the water's pH to the set point. Meanwhile, for controlling water turbidity, two 12V DC pumps are used, where one pump functions to discharge turbid water and the other to fill with clean water. The data read by the sensor can be monitored through the OLED screen. Based on the test results, the water quality control system for the goldfish aquarium using the fuzzy method can function well. Meanwhile, the water draining process takes 5 minutes and 20 seconds, and the clean water filling takes about 15 minutes and 24 seconds.